Diversifikasi olahan nira aren menjadi gula semut di Desa Gattareng Kabupaten Barru - Laelah Azizah; Ernawati S. Kaseng; Pince Salempa (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The aim of community service activities through the Community Partnership Program (PKM) is to provide knowledge and skills for the diversification of palm sugar processing, as well as the packaging and labeling process of brown sugar crafters in partner farmer groups. With the hope of motivating brown sugar artisans to develop ant sugar refined products and other processed products made from palm sap. The method of implementing community service activities through the Community Partnership Program (PKM), namely through counseling / socialization and training as well as with assistance. The results of the implementation of the Community Partnership Program (PKM) showed that the high activity of trainees and counselors in the question and answer session and discussion as well as demonstrations and application / field application related to the material on how to make ant sugar from the basic ingredients of palm sugar, indicated an increase in knowledge and skills community in Gattareng Village, Barru Regency. Increasing the knowledge and skills of the community also shows that through training and counseling in accordance with the local potential of their region will be able to change the mindset of the community, especially palm sugar crafters in PKM program farmer groups. The positive impact on increasing knowledge and skills in processing natural resources in the region is a form of community empowerment to increase their income and welfare.